2017
DOI: 10.2174/1874210601711010648
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of the Patterns of Third Molar Impaction in Panoramic Radiographs in Saudi Population

Abstract: Objectives:To evaluate the epidemiological patterns of third molar impaction in a cohort of patients living in the north of Saudi Arabia.Materials and Methods:A retrospective cohort study comprised of analysing 2550 Orthopantomograms (OPGs) belonging to patients who attended Aljouf University College of Dentistry between September 2013 and December 2015. OPGs were examined to determine the frequency of third molar impaction, their levels of eruption and angulations. Mixed effects logistic regression analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 13 publications
7
34
1
5
Order By: Relevance
“…These images show a large area of dental and facial tissues in one view. OPGs assist dentists in diagnosis and clinical decision-making concerning surgical interventions near vital structures, such as the inferior alveolar nerve, and the proximity of maxillary tooth roots to the sinus [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These images show a large area of dental and facial tissues in one view. OPGs assist dentists in diagnosis and clinical decision-making concerning surgical interventions near vital structures, such as the inferior alveolar nerve, and the proximity of maxillary tooth roots to the sinus [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on different cities in Saudi Arabia concluded and specified that orthopantomogram (OPG) radiography is a necessary image screening technique for teenagers and adults with permanent dentition. This simple technique can screen patient records because it is available in most dental centers and colleges of dentistry, well recognized by dental technicians, and can be used with software [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Two main classifications have been used to describe impacted third molars including Pell and Gregory's classification and Winter's classification. (3) In the Pell and Gregory's classification, impacted third molars are in "level A" if the occlusal surface of the impacted tooth is at the same level as the occlusal plane of the second premolar. These teeth are in "level B" if the occlusal plane is between the occlusal plane and the cervical line of the adjacent tooth.…”
Section: Introductionmentioning
confidence: 99%
“…(4) The Winter's classification, on the other hand, delineates the inclination of impacted third molars with regards to the long axis of the second molar. (3) According to the Winter's classification, an impacted third molar can be mesioangular (Ma), distoangular (Da), vertical (V), horizontal (H), or transverse (T). (3) A change in the position or the angulation of a third molar is common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation